2018
DOI: 10.1111/ajo.12764
|View full text |Cite
|
Sign up to set email alerts
|

Adopting innovation in gynaecology: The introduction of e‐consult

Abstract: E-consultation was effective at reducing the number of first outpatient face-to-face contacts without notable compromise of the quality of care or patient safety. E-consultation allows specialists to provide expert clinical guidance, management and support to the referring provider when appropriate. Topics for further study include patient benefits and satisfaction, and further assessment of the social, economic and financial impacts on all parties involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 8 publications
1
27
0
3
Order By: Relevance
“…An integrated maternal health system with shared electronic medical records and mobile technology tools can also make a significant contribution to COC through the enhancement of coordination between different healthcare providers at different levels and the provision of tailored maternity services [85, 86]. Mobile health (m-health) can potentially enhance pregnant women’s engagement with and trust in health professionals’ skills and can improve women-provider interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated maternal health system with shared electronic medical records and mobile technology tools can also make a significant contribution to COC through the enhancement of coordination between different healthcare providers at different levels and the provision of tailored maternity services [85, 86]. Mobile health (m-health) can potentially enhance pregnant women’s engagement with and trust in health professionals’ skills and can improve women-provider interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of new technology has proved to make mothers feel heard [87]. This requires the adoption of a new structure and the development of new practices based on collaboration to achieve the concept of “collective action” [85, 86].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the included studies were from 1 of 2 settings: 26 from the Champlain BASE program and 13 from VA settings. 7,[37][38][39][40][41][42][43][44][45][46][47][48] Of the remaining 24 studies, there were 12 from community health centers or large public health care systems, 43,[49][50][51][52][53][54][55][56][57][58][59] 8 from academic medical centers, [60][61][62][63][64][65][66][67] 2 from a nongovernmental humanitarian organization, 68, 69 1 from a not-for-profit integrated health care delivery system, 70 and 1 from a private company providing e-consult services. 71 Most studies were observational in design and lacked a control group.…”
Section: Methodsmentioning
confidence: 99%
“…61 Several studies employing manual review of the medical record found no increase in adverse events (eg, ED visits, hospitalizations, and/or death within 1-6 months) following e-consult. 40,55,60,[64][65][66] Among 500 patients referred for cardiology e-consults, 2.2% required hospitalization related to the problem addressed in the e-consult within 6 months; no comparable rate of hospitalization after face-to-face consults was provided. 40 A study of surgical e-consults reported that 4 of 36 patients who did not have clinic visits following e-consultation had ED visits for problems related to the initial reason for referral.…”
Section: Quality and Safety Outcomesmentioning
confidence: 99%
“…Electronic-consultations (e-consults), in which physicians communicate with specialists using secure email or web-based requests, provide an opportunity for family physicians to access clinical advice in a timely manner. Dermatology, gynecology, psychiatry, and rheumatology are among various health disciplines that have been serviced in e-consultations [5][6][7][8], though no studies are known to have examined the use of e-consultation to support SCI care. Reported benefits of e-consultation include quicker response time from specialist and thus more timely clinical care, decrease in unnecessary specialist visits, decrease in travel for patients and facilitation of knowledge translation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%